Efektivitas Model Pembelajaran Adaptif Berbasis AI Melalui Khan Academy dalam Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Zakariyah, M Fahmi; Rosyanafi, Rofik Jalal; Purwoko, Budi (Program Studi Pendidikan Luar Sekolah, 2025)
Abstract: This study aims to examine the effectiveness of AI-based adaptive learning through the Khan Academy platform in improving the academic performance of sixth-grade elementary school students. Using a quasi-experimental design, students were divided into two groups: the experimental group (using the Adaptive Learning Model) and the control group (using conventional methods). Data were collected through pre-tests, interventions, and post-tests using achievement tests, observation sheets, and questionnaires. The results showed a significant improvement in the experimental group (average score increased from 70.2 to 83.6), compared to the control group (from 71.5 to 75.3). The Mann-Whitney test confirmed a statistically significant difference between the groups (p < 0.05). These findings indicate that AI-based adaptive learning is more effective in enhancing student achievement. However, challenges in implementation such as limited access to digital devices, internet connectivity, and teacher readiness must be addressed. This research highlights the strategic role of adaptive learning technologies in bridging educational disparities and advancing equitable access to quality education in Indonesia and other developing countries. Abstrak: Penelitian ini bertujuan mengkaji efektivitas pembelajaran adaptif berbasis kecerdasan buatan (AI) melalui platform Khan Academy dalam meningkatkan hasil belajar siswa kelas VI SD. Menggunakan desain kuasi-eksperimen, siswa dibagi dalam dua kelompok: eksperimen (menggunakan Model Pembelajaran Adaptif) dan kontrol (menggunakan metode konvensional). Data dikumpulkan melalui pre-test, intervensi, dan post-test menggunakan tes hasil belajar, observasi, dan kuesioner. Hasil menunjukkan peningkatan signifikan pada kelompok eksperimen (rata-rata skor meningkat dari 70,2 menjadi 83,6), dibandingkan dengan kelompok kontrol (dari 71,5 menjadi 75,3). Uji Mann-Whitney mengonfirmasi perbedaan signifikan antar kelompok (p < 0,05). Temuan ini menegaskan bahwa pembelajaran adaptif berbasis AI lebih efektif dalam meningkatkan hasil belajar siswa. Namun, tantangan implementasi seperti keterbatasan perangkat, konektivitas, dan kompetensi guru perlu mendapat perhatian. Penelitian ini menegaskan pentingnya teknologi pembelajaran adaptif sebagai strategi untuk mengurangi kesenjangan pendidikan dan memperluas akses pembelajaran berkualitas di Indonesia maupun negara berkembang lainnya.